Strategi Pemasaran Inovatif untuk Menarik Wisatawan ke Wisata Pemandian Jang Oden - Pamukti, Hakiki; Sari, Lilis Permata; Rossi, Lola Valentina; Saputri, Selfi; Gumano, Hendry Natanael; Purnamasari, Endah Dewi; Anggraini, Leriza Desitama (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
One of the villages that has tourism potential in Lembak Regency is Kemang Village. Jang Oden Bathing Tourism is a tourist destination with unique natural beauty, but due to lack of marketing, it is not well known to many tourists. Therefore, innovative marketing strategies need to be introduced to increase tourist visits. The methodology used in this activity is a participatory approach and the implementation of effective innovative marketing strategies. carried out through the use of social media such as Instagram to promote the tourist destination. Google Maps marketing is also used to improve accessibility. Refreshing promotional packages equipped with free karaoke facilities can be an additional attraction. The results of this service have a positive impact after marketing on Instagram, showing that this strategy is effective in increasing awareness and tourist visits to this tourist destination.